Association of outpatient use of renin–angiotensin–aldosterone system blockers on outcomes of acute respiratory illness during the COVID-19 pandemic: a cohort study. Issue 7 (6th July 2022) - Jeffery, Molly Moore; Oliveira J e Silva, Lucas; Bellolio, Fernanda; Garovic, Vesna D; Dempsey, Timothy M; Limper, Andrew; Cummins, Nathan W
Abstract : Objectives: Evaluate the associations between patients taking ACE inhibitors and angiotensin receptor blockers (ARBs) and their clinical outcomes after an acute viral respiratory illness (AVRI) due to COVID-19. Design: Retrospective cohort. Setting: The USA; 2017–2018 influenza season, 2018–2019 influenza season, and 2019–2020 influenza/COVID-19 season. Participants: People with hypertension (HTN) taking an ACEi, ARB or other HTN medications, and experiencing AVRI. Main outcome measures: Change in hospital admission, intensive care unit (ICU) or coronary care unit (CCU), acute respiratory distress (ARD), ARD syndrome (ARDS) and all-cause mortality, comparing COVID-19 to pre-COVID-19 influenza seasons. Results: The cohort included 1 059 474 episodes of AVRI (653 797 filled an ACEi or ARB, and 405 677 other HTN medications). 58.6% were women and 72.9% with age ≥65. The ACEi/ARB cohort saw a larger increase in risk in the COVID-19 influenza season than the other HTN medication cohort for four out of five outcomes, with an additional 1.5 percentage point (pp) increase in risk of an inpatient stay (95% CI 1.2 to 1.9 pp) and of ICU/CCU use (95% CI 0.3 to 2.7 pp) as well as a 0.7 pp (0.1 to 1.2 pp) additional increase in risk of ARD and 0.9 pp (0.4 to 1.3 pp) additional increase in risk of ARDS. There was no statistically significant difference in the absolute risk of death (−0.2 pp, 95% CI −0.4 to 0.1 pp). However, the relative risk of death in 2019/2020 versus 2017/2018 for the ACEi/ARB group was larger (1.40 (1.36 to 1.44)) than for the other HTN medication cohort (1.24 (1.21 to 1.28)). Conclusions: People with AVRI using ACEi/ARBs for HTN had a greater increase in poor outcomes during the COVID-19 pandemic than those using other medications to treat HTN. The small absolute magnitude of the differences likely does not support changes in clinical practice.